In Vitro Pharmacological Profile of a New Small Molecule Bradykinin B2 Receptor Antagonist - Lesage, Anne; Gibson, Christoph; Marceau, François; Ambrosi, Horst-Dieter; Saupe, Jörn; Katzer, Werner; Loenders, Brigitte; Charest-Morin, Xavier; Knolle, Jochen (Frontiers in Pharmacology, 2020)
We here report the discovery and early characterization of Compound 3, a representative of a novel class of small molecule bradykinin (BK) B2 receptor antagonists, and its superior profile to the prior art B2 receptor antagonists Compound 1 and Compound 2. Compound 3, Compound 2, and Compound 1 are highly potent antagonists of the human recombinant B2 receptor (Kb values 0.24, 0.95, and 1.24 nM, respectively, calcium mobilization assay). Compound 3 is more potent than the prior art compounds and icatibant in this assay (Kb icatibant 2.81 nM). The compounds also potently inhibit BK-induced contraction of endogenous B2 receptors in a human isolated umbilical vein bioassay. The potencies of Compound 3, Compound 2, Compound 1, and icatibant are (pA2 values) 9.67, 9.02, 8.58, and 8.06 (i.e. 0.21, 0.95, 2.63, and 8.71 nM), respectively. Compound 3 and Compound 2 were further characterized. They inhibit BK-induced c-Fos signaling and internalization of recombinant human B2 receptors in HEK293 cells, and do not antagonize the venous effects mediated by other G protein-coupled receptors in the umbilical vein model, including the bradykinin B1 receptor. Antagonist potency of Compound 3 at cloned cynomolgus monkey, dog, rat, and mouse B2 receptors revealed species selectivity, with a high antagonist potency for human and monkey B2 receptors, but several hundred-fold lower potency for the other B2 receptors. The in vitro off-target profile of Compound 3 demonstrates a high degree of selectivity over a wide range of molecular targets, including the bradykinin B1 receptor. Compound 3 showed a lower intrinsic clearance in the microsomal stability assay than the prior art compounds. With an efflux ratio of 1.0 in the Caco-2 permeability assay Compound 3 is predicted to be not a substrate of efflux pumps. In conclusion, we discovered a novel chemical class of highly selective and very potent B2 receptor antagonists, as exemplified by Compound 3. The compound showed excellent absorption in the Caco-2 assay, predictive of good oral bioavailability, and favourable metabolic stability in liver microsomes. Compound 3 has provided a significant stepping stone towards the discovery of the orally bioavailable B2 antagonist PHA-022121, currently in phase 1 clinical development.